(untitled) - Jill Hadfield (London, 1995)
The book examines the characteristics of a successful group, and suggests pratical ways in which a teacher can foster a cohesive and supportive classroom atmosphere of the kind conducive to learning. There are activities suitable for classes of all levels of general or specilized English courses
Keywords: english language - study and teaching